2000
DOI: 10.1002/1520-7560(2000)9999:9999<::aid-dmrr143>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oedema during treatment of diabetic ketoacidosis: are we any nearer finding a cause?

Abstract: Cerebral oedema remains the leading cause of death and morbidity in children with Type 1 diabetes mellitus. Around seven per thousand episodes of diabetic ketoacidosis (DKA) are complicated by cerebral oedema, and one-quarter of those children will die from it. The cause or causes of cerebral oedema are still very poorly understood, but lawyers are already keen to implicate various aspects of the management of DKA. There have been many theories as to the pathophysiology of cerebral oedema, and possible contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 85 publications
5
71
0
2
Order By: Relevance
“…Clinical studies have linked newly diagnosed diabetes, young age, low blood CO 2 , high blood urea nitrogen, and administration of bicarbonate to the development of DKA-CE (5,8,9). While these epidemiologic studies may identify children at risk for developing of DKA-CE, animal translational studies will provide insight into the cellular mechanisms contributing to DKA-CE.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Clinical studies have linked newly diagnosed diabetes, young age, low blood CO 2 , high blood urea nitrogen, and administration of bicarbonate to the development of DKA-CE (5,8,9). While these epidemiologic studies may identify children at risk for developing of DKA-CE, animal translational studies will provide insight into the cellular mechanisms contributing to DKA-CE.…”
supporting
confidence: 77%
“…Free water was not actively administered to the DKA mice in our study, which could explain the significantly lower BWC than control mice. Our model therefore examined only DKA-CE associated with DKA treatment (5,6,8). Of note, the DKA treatments in this study were administered as a single i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Because symptoms of increased intracranial pressure often become apparent during DKA treatment, many investigators hypothesized that rapid changes in serum osmolality and/or rapid fluid infusion during DKA treatment are responsible (28,32,33). This hypothesis has been questioned, however, because studies (5,6,10) have documented the occurrence of both subclinical CE and overt, symptomatic CE before DKA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology is still unclear though recent hypotheses suggest that, as extracellular fluid hyperosmolarity and dehydration increase, the brain accumulates intracellular, osmotically active molecules (including glucose and unidentified molecules collectively http://pmj.bmj.com/ termed ''idiogenic osmoles'') that maintain cellular volume. [65][66][67] In addition intracellular acidosis (possibly exacerbated by the passage of ketone bodies into cells as well as hypoxia) leads to intracellular sodium accumulation as hydrogen is extruded from the cells by the sodium/hydrogen membrane pump. If extracellular osmolarity falls at a rate exceeding that at which the brain can excrete its accumulated idiogenic osmoles, then oedema occurs.…”
Section: Complicationsmentioning
confidence: 99%
“…If extracellular osmolarity falls at a rate exceeding that at which the brain can excrete its accumulated idiogenic osmoles, then oedema occurs. [65][66][67] The idea that the treatment of DKA itself might be the cause of cerebral oedema has gained support over the years, but no single aspect of therapy has been implicated in studies to date and cerebral oedema has been shown to be present before treatment even begins. 51 68 Low partial pressures of arterial carbon dioxide, high serum urea, and bicarbonate therapy are the risk factors most predictive of cerebral oedema, 51 though these may merely reflect the severity and duration of DKA in those who subsequently develop this complication.…”
Section: Complicationsmentioning
confidence: 99%